Cost-optimal nZEB reform strategies and the influence of building orientation for Mediterranean university buildings: case study of the University of Málaga - Da Costa Duarte, Danela Carolina; Rosa-Jiménez, Carlos (Elsevier BV, 2022)
The Energy Performance of Buildings Directive (EPBD) requires the transformation of European buildings into nearly zero-energy buildings (nZEBs) before 2050 as a mitigation strategy against the imminent climate emergency. This paper aims to determine the cost-optimal nZEB reform strategy for Spanish university buildings located in the Mediterranean climate, evaluating the influence of the building's orientation on nZEB cost optimality. The present work carries out a case study on three similar buildings at the University of Málaga. The optimal cost-efficiency nZEB reform strategy is determined, rigorously maintaining the formal design of the building through energy simulations with Sefaira Systems software under the EPBD framework. Six reform options were proposed to determine the cost-optimal strategy meeting nZEB requirements for each building. The results show that the most profitable strategy is to improve the efficiency of the thermal envelope and the HVAC system, reducing the energy consumption of the studied buildings by 85–93%. Although a general strategy for nZEB renovations was identified, building orientation proved to be a governing factor in energy performance. As such, the cost-optimal reform strategy was found to be specific to each particular building.
Keywords: Edificios - Conservación de la energía; Universidad de Málaga - Edificios - Conservación de la energía; Nearly zero-energy building (nZEB); Energy simulation; Cost-optimal level; Energy savings; Retrofitting strategies